A novel RFLP method for identification of morphologically similar avian Sarcocystis species - Sneideris, Donatas; Stalpes, Monika; Butkauskas, Dalius; Prakas, Petras (Parasitology research (1987), 2022)
Protozoans of genus Sarcocystis are widespread parasites infecting mammals, birds, and reptiles. Morphology of their sarcocysts is an important criterion for species identification. However, as more and more morphologically similar Sarcocystis species are being found and described, additional methods for their routine diagnostics are needed. We investigated restriction fragment length polymorphism (RFLP) as potential alternative to sequencing data analysis for the identification of Sarcocystis species using birds as an intermediate host. The internal transcribed spacer 1 (ITS1) region sequences of seventeen Sarcocystis species ( S. albifronsi , S. anasi , S . calchasi , S . columbae , S . cornixi , S . corvusi , S. cristata , S . halieti , S. falcatula , S . fulicae , S . kutkienae , S . lari , S. lindsayi , S. rileyi , S . turdusi , S.wenzeli , and S . wobeseri ) of interest were analysed and five best-fitting endonucleases generating most informative restriction fragments were selected for routine testing. In general, RFLP analyses are always inconclusive as they target very short DNA sequences. However, it can be an irreplaceable technique when fast and cheap identification and discrimination of known species are required, which was our main goal and preliminary results indicate that RFLP could be successfully used when identifying closely related avian Sarcocystis species with just two nucleases.